Pengaruh Pengalaman Pelanggan dan Persepsi Harga Terhadap Minat Beli Ulang Produk - Nurul Izzah, Berliana; Purwanto, Sugeng; Fitriyah, Zumrotul (Akuisisi : Jurnal Akuntansi, 2023)
Deodorant is the one of the main alternatives for the community in overcoming the problem of bad body odor. The large number of deodorant products with various brands in circulation, makes the competition in the deodorant industry in the market share even tighter. One of the most famous deodorant products in Indonesia is Rexona. This study aims to determine the influence of customer experience and price perception on repurchase interest of Rexona deodorant products in the city of Surabaya. The sample used in this study were buyers and users of Rexona deodorant for 2 (two) users times in the city of Surabaya as many as 100 people. The sampling method used is non-probability sampling with purposive sampling. The analysis technique used is Partial Least Square (PLS). Data collected from questionnaire results using the likert method are used to test the validity and reliability of the data. The research results show that customer experience and price perception have a positive effect on repurchase interest of Rexona deodorant products in the city of Surabaya.